Analysis of Quick Smash Ability of Men's Volleyball Players of the Volleyball UKM STKIP Hermon Timika - Nurwirhanuddin, Nurwirhanuddin; Letisia, Maria; Lae Laem, Yohanis Fredi (JUPE : Jurnal Pendidikan Mandala, 2025)
The purpose of this study was to determine the quick smash ability of male volleyball players of the Volleyball UKM STKIP Hermon Timika. This type of research is a quantitative descriptive study because the researcher wants to know the description of the quick smash ability of male volleyball players of the Volleyball UKM STKIP Hermon Timika. Based on the results of quantitative descriptive analysis of the data obtained, the sum value of the quick smash ability of male volleyball players of the Volleyball UKM STKIP Hermon Timika is 1072. The mean value of the quick smash ability of male volleyball players of the Volleyball UKM STKIP Hermon Timika is 67. The minimum value of the quick smash ability of male volleyball players of the Volleyball UKM STKIP Hermon Timika is 50. The maximum value of the quick smash ability of male volleyball players of the Volleyball UKM STKIP Hermon Timika is 88. The standard deviation of the quick smash ability of male volleyball players of the Volleyball UKM STKIP Hermon Timika is 12,754. The variance value of the quick smash ability of male volleyball players of the Volleyball UKM STKIP Hermon Timika is 162,667. Furthermore, the description of the quick smash ability category of male volleyball players of the Volleyball UKM STKIP Hermon Timika shows that the very good, good, and sufficient categories, respectively, show that the frequency value of 0 percentage is 0%, the frequency of 4% is 25%, and the frequency of 2% is 12.5. While in the less and very less categories, the frequency and percentage values are the same, namely, the frequency of 5 percent is 31.25. Of the 16 players, only 6 people are not in the less and very less category in doing quick smashes; the rest are in the less and very less category, with a total of 10 players. The results of this study can be concluded that the quick smash ability category of male volleyball players of Volleyball UKM STKIP Hermon Timika is in the less and very less category.